Psychophysiological Methods in Language Research Rethinking Embodiment in Studies of Linguistic Behaviors - Hardacre, Bahiyyih (Lexington Books, 2020)
This book is a guide for language researchers who are considering the adoption of a transdisciplinary and multidimensional approach to language research. It aims to provide a n overview of each of the most popular physiological methods today, along with their applications in research, and basic data collection procedures.